Construction of tripeptide heteroligand library as capturing agent for mercury plasmonic detection - Ku Ismail, Ku Syaridatul Irma (2022)
Mercury is one of the priority metals classified as a human carcinogen by the US Environmental Protection Agency and the International Agency for Research on Cancer. This metallic element has a high degree of toxicity and is known to induce multiple organ damage and have severe adverse effects on human health and the environment, even at low levels of exposure. It has many forms in the soil, including inorganic and organic mercury. In this work, two novel tripeptides were designed and synthesized based on the amino-terminal Cu2+ and Ni2+ binding (ATCUN) motif. Two systems, namely monoligand and heteroligand systems, were compared in this work. Tripeptides were individually immobilized onto gold nanoparticles (AuNPs) surfaces via covalent coupling. In a monoligand system, only a particular tripeptide-AuNPs will be used as capturing agents for Hg2+, while in a heteroligand system, two different tripeptide- AuNPs will be used simultaneously in a mixture. The heteroligand system was found to be more effective compared to the monoligand system. The interaction of heteroligand enhances the selectivity and sensitivity of the plasmonic sensor for Hg2+. Upon the addition of metal ions, the red-to-blue color change and the degree of AuNPs aggregation formed by the heteroligand system were doubled when compared to the monoligand system. These two novel tripeptides: 0.10 mM of pH 9 DCH (aspartic acid- cysteinehistidine) and 0.20 mM of pH 11 HCD (histidine-cysteine-aspartic acid) were selected among eleven novel tripeptides and one commercial tripeptide as the best capturing agents for Hg2+ with an absorbance ratio (A683/A524) of 1.098. The finding was supported by UV-Vis spectra, Dynamic Light Scattering (DLS) spectroscopy, and Transmission Electron Microscopy (TEM) analysis. The limit of detection (LOD) for Hg2+ detection was 0.025 parts per millions (ppm) with absorbance reading of 0.094. This new approach can constitute a more effective detection system targeting small molecules such as amino acids, metal ions and fatty acids.